Moringa oleifera non-conventional therapy to help breast milk production as an effort to achieve exclusive reastfeeding at the Deby Independent Midwife Practice, Medan City - Lasria Simamora; Mediana Beru Sembiring; Riska Susanti Pasaribu; Riani Mawardah; Titine Juniati Situmorang (Science Midwifery, 2023)
Exclusive breastfeeding is an effort to improve the nutritional status of children in the first 1000 days of birth. Nationally, the percentage of babies aged less than 6 months who receive exclusive breastfeeding in Indonesia is 72.04%, for North Sumatra it is 57.17% and has still not reached the target of providing exclusive breastfeeding. The aim of this research is to determine the effectiveness of Moringa leaf juice in increasing breast milk production to reduce the use of modern medicine and support the achievement of exclusive breastfeeding. This research is a case control study using Moringa leaf juice which was carried out from May to August 2023. The research subjects were postpartum mothers who were willing to be samples. Patient data collection was carried out at the Deby Midwife Practice. The respondents were 30 postpartum mothers, of which 15 respondents were in the intervention group and 15 respondents were in the control group. The results of statistical analysis of the paired t test data showed a significance value (ρ) of 0.000 (<0.05) so it can be concluded that Ha was accepted and Ho was rejected, which means there was an increase in breast milk production after giving Moringa leaf juice. It is hoped that health workers involved in maternal and child health will promote the use of Moringa leaves to increase breast milk production.